2020
DOI: 10.1002/ccr3.2583
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term ungrounded cable support for short‐to‐shield syndrome

Abstract: Short‐to‐shield (STS) is a potential complication for left ventricular assist device (LVAD) patients supported by the HeartMate II (HMII) pump. This phenomenon occurs when a damaged internal wire within the driveline makes contact with the surrounding sheath, resulting in insufficient power delivery to the motor when connected to a grounded power base unit (PBU). An ungrounded cable can be used to negate these effects, but the long‐term safety of this treatment strategy is unknown. In this case series, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…20 This eliminates the short to shield, but still leaves the possibility of a phase to phase short which could also lead to a pump stop. 21 In the HM 3 driveline this copper shield has been eliminated and is replaced by a tough synthetic fiber protection layer. Our study showed no driveline failures during follow-up in the HM 3 devices, albeit with a shorter follow-up, suggesting the increased reliability of the fiber protection layer over the copper mesh.…”
Section: Discussionmentioning
confidence: 99%
“…20 This eliminates the short to shield, but still leaves the possibility of a phase to phase short which could also lead to a pump stop. 21 In the HM 3 driveline this copper shield has been eliminated and is replaced by a tough synthetic fiber protection layer. Our study showed no driveline failures during follow-up in the HM 3 devices, albeit with a shorter follow-up, suggesting the increased reliability of the fiber protection layer over the copper mesh.…”
Section: Discussionmentioning
confidence: 99%